INTERNALIZING AND EXTERNALIZING PROBLEMS IN STUDENTS: PROBLEMAS INTERNALIZANTES E EXTERNALIZANTES EM ESTUDANTES UNIVERSITÁRIOS - Larangeira Carvalho, Priscila; Ribeiro de Araújo, Fernanda; Ramos Martins, Fernando; Eduardo Scachetti, Rodolfo; RAMACCIOTTI DE OLIVEIRA MONTEIRO, NANCY (Revista Interdisciplinar de Estudos em Saúde, 2025)
National and international studies point to psychological difficulties in university students, people that face their own developmental challenges in the transition to adulthood. The study aimed at identifying Externalizing and Internalizing psychological problems in undergraduate students from different areas of knowledge. The Adult Self-Report was used to investigate 1,336 students between 18 and 59 years old, being 59.1% of them women, from universities in the state of São Paulo Brazil. Descriptive and inferential statistical analysis was performed. Results indicated borderline/clinical ranges in Internalizing problems for 34.55% of men and 51.83% of women; in Externalizing problems for 24.71% of men and 35.23% of women. Problems reached higher scores in the Social Sciences, Journalism and Information area. Results related to anxiety and depression in university students were according to literature, indicating greater vulnerability among female students. New studies are suggested to investigate whether such problems are due to insertion in higher education. KEYWORDS: Adults; students; mental health. Rbstract Estudos nacionais e internacionais apontam dificuldades psicológicas em estudantes universitários, grupo que enfrenta desafios próprios do desenvolvimento na transição à fase adulta. O objetivo deste estudo foi avaliar problemas psicológicos externalizantes e internalizantes em graduandos de diferentes cursos universitários. Com uso do Adult Self-Report, foram avaliados 1.336 estudantes (18 a 59 anos) de universidades do estado de São Paulo, 59,1% mulheres. Analisados por estatística descritiva e inferencial, dados indicaram faixas limítrofe/clínica em problemas internalizantes para 34,55% dos homens e 51,83% das mulheres, e em problemas externalizantes para 24,71% dos homens e 35,23% das mulheres. Estudantes de cursos da área Ciências Sociais, Jornalismo e Informação apresentaram maiores escores de problemas. Os resultados relacionados à ansiedade e depressão nas universitárias foram concordantes com a literatura, apontando maior vulnerabilidade entre estudantes mulheres. Novos estudos ficam sugeridos para investigar se tais problemas são decorrentes da inserção no ensino superior. PALAVRAS-CHAVE: Adultos; Estudantes; Saúde Mental.